Reliability and Validity of the Chinese Version of the Ventilator‐Associated Pneumonia Prevention Knowledge and Attitudes Scale: A Short Research Report - Zhiqiang Cheng; Jiaoyun Xia; Yuxuan Zeng; Jing Li; Xueyan Wei; Baozhen Zhang (Nursing in Critical Care, 2026)
ABSTRACT Ventilator‐associated pneumonia (VAP) remains a prevalent and costly healthcare‐associated infection in intensive care units (ICUs). This study aimed to translate the Ventilator‐Associated Pneumonia Prevention Knowledge and Attitudes Scale (VAPPKAS), conduct cross‐cultural adaptation and test its psychometric properties. A cross‐sectional survey was performed, enrolling 322 ICU nurses from one tertiary hospital in Jiangxi Province. The Chinese VAPPKAS consists of two dimensions containing 15 items. The Cronbach's α coefficient was 0.937, split‐half reliability was 0.928, and test–retest reliability was 0.907 (95% CI: 0.887–0.924). The item‐level content validity index (I‐CVI) ranged from 0.867 to 1.000, and the average scale‐level content validity index (S‐CVI/Ave) reached 0.906. Exploratory factor analysis (EFA) extracted two factors that jointly explained 76.382% of the total variance. Confirmatory factor analysis (CFA) yielded satisfactory model fit indices: χ 2 /df = 2.326, RMSEA = 0.052, SRMR = 0.026, NFI = 0.927, TLI = 0.918, CFI = 0.922, GFI = 0.903. The Chinese version of the VAPPKAS demonstrates excellent reliability and validity.